Ethological Representation of Birds and Other Animals in Kidung Tantri Kediri - Yusi Nurcahya Dewi; Sri Harti Widyastuti; Anwar Efendi; Suwardi Suwardi; Yuyun Farida (Javanologi: International Journal of Javanese Studies, 2025)
Kidung Tantri Kediri is one of the titles of a collection of tantri stories written in Middle Javanese language. Kidung Tantri Kediri text which used in this research is the text of Kidung Tantri Kediri edited by Revo Arka Giri Soekatno. The manuscript identification in the text editing also states that Kidung Tantri Kediri is a prose text composition of Kidung Tantri Kamandaka. This study aims to explore the ethological representation within Kidung Tantri Kediri’s text. The analysis in this study uses intertextual studies with the discipline of ethology that studies animal behavior. The data collected by determining the dominance of animals that often appear in the text and other distinctive features. Furthermore, the results of the intertextuality study are then analyzed using semiotics to determine the philosophical meaning contained in the representation. Finally, the research concludes that the ethology represented within Kidung Tantri Kediri’s text. The animal characters are analogized philosophically in the story.